Dual solutions for double diffusion and MHD flow analysis of micropolar nanofluids with slip boundary condition - Khan, Y.; Majeed, Afraz Hussain; Rasheed, Muhammad Afraz; Alameer, A.; Shahzad, Hasan; Irshad, Sadia; Faraz, N. (Frontiers in Physics, 2022)
The present communication is designed to elucidate the flow attributes of micro-polar non-Newtonian liquid over stretching/shrinking surfaces. In addition, we have observed the stagnation aspect along with the velocity slip condition on the momentum field. The Fourier law of heat conduct, along with a physical aspect of stratified and heat generation absorption, are then used to model the temperature equation. The Buongiorno nanofluid model is used to study additional transport features. After a discussion of PDEs using similarity transformation, mathematical formulations of the given problem are supported in the form of an ordinary differential system. The solution of modeled governing equations containing physical effects is simulated by using the shooting method in conjunction with RK- Method. The significant effects of flow parameters that are associated with velocity, temperature, and concentration distribution for low and upper branch solutions are revealed through graphs and tables. Quantities of engineering concerns like skin friction coefficient and Nusselt number are also compared with previous results of critical values. Furthermore, it should be considered that as the micro-pole parameters are increased, the local skin friction coefficient and the local Nusselt number amplitude also rise.